Short-term antidepressant treatment and facial processing. Functional magnetic resonance imaging study. - Norbury, R; Mackay, C; Cowen, P; Goodwin, G; Harmer, C (2007)
We used functional magnetic resonance imaging to investigate the effects of short-term treatment with reboxetine, a selective noradrenaline reuptake inhibitor, on emotional facial processing in healthy volunteers. Reboxetine was associated with a reduced amygdala response to fearful faces and increased activation to happy v. neutral facial expressions in the right fusiform gyrus, relative to placebo treatment and in the absence of changes in mood. Our results show that reboxetine modulates the neural substrates of emotional processing, highlighting a mechanism by which drug treatment could normalise negative bias in depression and anxiety.